A Motor Control Trainer for Use in a University Agricultural Electricity Course - Rice, Lanny E.; Johnson, Donald M. (Journal of Agricultural Systems, Technology, and Management, 2020)
Electricity is an important technical subject in university agricultural systems management programs and motor control is an important unit of instruction within such courses. In order to provide efficient hands-on student experiences with planning and wiring motor control circuits, six motor control trainers were designed and constructed for use in an agricultural electricity course (ASTM 3173). The design criteria for the trainers were that they: (1) be safe for student use, (2) contain multiple control devices, (3) allow for easy attachment of circuit wires, and (4) cost no more than $650.00 per trainer. The trainers, as constructed, met each design criterion.